Numerical and experimental investigation of flow properties of generator cabinets - ATMACA, MUSTAFA (My University, 2023)
This study aimed to reveal predictions about how the total pressure difference occurring in front of and behind the radiator in the cabin generator set affects the operating temperature of the generator set in the absence of sufficient thermal information. After the cabin design, numerical analyses were made for three louvers with different depth dimensions, as that they significantly affect the total pressure difference. It was found the most suitable louver depth as a result of numerical analysis. Flow analyses were created by using ANSYS FLUENT 19.2 software as a numerical study of the generator cabin. Numerical analyses haven\"t been created based on temperature since thermal information was not adequately available. As a result of numerical studies, a total pressure difference of 139.25 Pa has occurred. This pressure difference value is 14.25 Pa higher than the pressure difference value allowed by the radiator of the 1104C-44TAG2 engine. Firstly, the generator set was manufactured. Then it was implemented experimental studies with the HIOKI test device to determine how the pressure difference value of 14.25 Pa affects the temperature of the generator set. The result shows that the pressure difference of 14.25 Pa reduces the maximum ambient temperature at which the generator can operate by 3.9 degrees C as a result of the experimental studies
Keywords: Harita Mühendisliği-Geomatik; Mühendislik ve Teknoloji; Geotechnical Engineering; Engineering and Technology; MÜHENDİSLİK, ÇOK DİSİPLİNLİ; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENGINEERING, MULTIDISCIPLINARY; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Medya Teknolojisi; Mühendislik (çeşitli); Fizik Bilimleri; General Engineering; Media Technology; Engineering (miscellaneous); Physical Sciences; Generator cabinet; louver; numerical analysis; dimensional comparison; cfd